Some properties of multiparameter random fields - Bondarev, B. V.; Zhirnyi, G. G. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study some properties of multiparameter random fields, namely, the problems of absolute continuity of measures and averaging in the multiparameter case. For a special stochastic system, we present inequalities of large deviations.